2016
DOI: 10.1088/1748-0221/11/01/c01040
|View full text |Cite
|
Sign up to set email alerts
|

Design of Si-photonic structures to evaluate their radiation hardness dependence on design parameters

Abstract: HL-LHC will require new optical data transmitters that can provide high data rates and be resistant against high levels of radiation. Furthermore, new design paths for future optical readout systems for HL-LHC could be opened if there was a possibility to integrate the optical components with their driving electronics and possibly also the silicon particle sensors themselves. All these functionalities could potentially be combined in the silicon photonics technology which currently receives a lot of attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…With the knowledge gained in [14], further experiments were performed using the same customized silicon MZMs described there and in greater detail in [13]. The cross section of the modulator used is shown in Fig.…”
Section: Test Samples and Measurement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…With the knowledge gained in [14], further experiments were performed using the same customized silicon MZMs described there and in greater detail in [13]. The cross section of the modulator used is shown in Fig.…”
Section: Test Samples and Measurement Proceduresmentioning
confidence: 99%
“…The previous work has shown that SiPh MZMs are relatively insensitive to neutron radiation [10], [11], but they show strong degradation with the ionizing X-ray radiation [12]. Understanding of the radiation damage mechanisms in SiPh MZMs led to the design of custom MZMs [13] that have been shown to be significantly more radiation tolerant [14]. Fully optimized devices have been shown to be able to withstand a TID of up to 3.2 MGy (unbiased measurement), albeit with a larger initial device insertion loss.…”
Section: Introductionmentioning
confidence: 99%
“…The SiPh MZMs used for all tests were designed by us and fabricated by imec [11] as part of a multiproject wafer (MPW) run offered through ePIXfab [12]. The detailed design parameters of the MZMs are described in [9]. The investigated GeSi PDs were building-block devices designed by imec.…”
Section: Test Samples and Measurement Procedures A Devicesmentioning
confidence: 99%
“…SiPh MZMs with such a conventional design could not be installed in the innermost detector regions of future HEP experiments due to their high sensitivity to ionizing radiation. Previously, we presented a custom-designed SiPh test chip that included several MZMs with varied design parameters [9] to assess whether the resistance against ionizing radiation can be improved through [5]. The data for the X-ray irradiation were taken from [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that silicon photonics Mach-Zehnder modulators (MZMs) are relatively insensitive to neutron radiation, but show strong degradation with ionizing X-ray radiation. It was further presented, that with customized MZM designs, increasing the rib height of MZMs (shallow-etch device), the resistance against X-ray radiation can be improved [2,3,4,5,6]. Recently, the influence of forward biasing on the radiation hardness was reported and a strong post-irradiation annealing effect was demonstrated [7].…”
Section: Introductionmentioning
confidence: 99%